Analisis Motivasi Belajar Peserta Didik Kelas VI Pada Mata Pembelajaran IPA di SDN 007 Pendalian IV Koto - Indah Maslakhatul Ni’ma (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study aims to determine how much learning motivation students in class VI at SDN 007 Pendalian IV Koto. The research used descriptive qualitative research methods. Data analysis of science learning motivation was collected using non-test techniques in the form of a questionnaire with 15 statement items. The results showed that the learning motivation of grade VI students in learning science at SDN 007 Pendalian IV Koto was categorized as good. Where out of 17 students get an average score of 70.3. Learning motivation of students must certainly be improved again by the teacher, because with the increase in learning motivation of students, it will also increase student learning outcomes.